2010
DOI: 10.1016/j.molcel.2010.07.029
|View full text |Cite
|
Sign up to set email alerts
|

MMXD, a TFIIH-Independent XPD-MMS19 Protein Complex Involved in Chromosome Segregation

Abstract: Xeroderma pigmentosum group D (XPD) protein is one of the subunits of TFIIH that is required for nucleotide excision repair and transcription. We found a XPD protein complex containing MMS19 that was assumed to be a regulator of TFIIH. However, the MMS19-XPD complex did not contain any other subunits of TFIIH. Instead, it included FAM96B (now designated MIP18), Ciao1, and ANT2. MMS19, MIP18, and XPD localized to the mitotic spindle during mitosis. The siRNA-mediated knockdown of MMS19, MIP18, or XPD led to imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
133
1
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(146 citation statements)
references
References 28 publications
11
133
1
1
Order By: Relevance
“…The XPD helicase functions as a component of TFIIH but also can be found associated with non-TFIIH complexes that play roles in processes other than transcription and DNA repair. The MMXD complex is composed of XPD, MMS19, MIP18, Ciao1, and ANT2 and is involved in chromosome segregation and nuclear-shape formation (49). XPD also associates with CAK in the absence of the other TFIIH subunits, regulating the localization of CAK on its substrate and therefore its activity (50).…”
Section: Discussionmentioning
confidence: 99%
“…The XPD helicase functions as a component of TFIIH but also can be found associated with non-TFIIH complexes that play roles in processes other than transcription and DNA repair. The MMXD complex is composed of XPD, MMS19, MIP18, Ciao1, and ANT2 and is involved in chromosome segregation and nuclear-shape formation (49). XPD also associates with CAK in the absence of the other TFIIH subunits, regulating the localization of CAK on its substrate and therefore its activity (50).…”
Section: Discussionmentioning
confidence: 99%
“…Purification of Protein Complexes-The FLAG-His 6 -MMS19 complex was purified from HEK293 cells overexpressing FLAG-His 6 -MMS19 as described previously (17). The complex between FLAG-His 6 -MMS19 and HA-CIAO1 was purified by sequential affinity purification with anti-FLAG M2-agarose (Sigma-Aldrich), followed by anti-HA agarose (Sigma-Aldrich), as described previously (19).…”
Section: Methodsmentioning
confidence: 99%
“…Previously, we reported that human MMS19 and XPD form a novel TFIIH-independent protein complex, which we named MMXD, consisting of MMS19, XPD, MIP18, ANT2, and CIAO1 (17). CIAO1 is involved in the late step of cytosolic iron-sulfur cluster assembly (CIA) (18).…”
mentioning
confidence: 99%
“…Thus, miRNAs targeting TFIIHcoding mRNAs could, in principle, modulate the availability of different subunits favoring the formation of differential TFIIHderived subcomplexes. Supporting the notion that different subcomplexes coexist, it has been recently shown that the XPD subunit is part of a different complex, termed MMXD (38), involved in chromosomal segregation. In addition, it has been shown that members of the proteosome pathway interact with particular CAK components regulating its degradation (39).…”
Section: Discussionmentioning
confidence: 94%